Active disturbance rejection control based on EID compensation for LFC with communication delays. (30th December 2018) - Liu, Fang; Xu, Zhuang; Li, Yong; Sidorov, Denis
Abstract: An active disturbance rejection control (ADRC) based on equivalent input disturbances (EID) for load frequency control (LFC) is proposed for power system with communication delays. This method can eliminate the influence of parameter uncertainty and load variation, and ensure high dynamic performance by compensation of EID. The proposed method can effectively compensate kinds of disturbance, neither need the characteristic information of the disturbance nor need the inverse model of the plant. The state of the controlled object is reconstructed by the improved state observer, and then the state space model of the close-loop time delay power system is established. The system stability conditions are given in the form of LMI and the parameters of the controller are obtained. Finally, simulation results show the proposed method is significant to maintain system stability and validate its robustness and effectiveness.